Signaling pathways in glioblastoma - Gomes, Isabella [UNESP] (2025)
Cancer is one of the main public health problems worldwide. Among tumors of the Central Nervous System (CNS), glioblastoma (GBM) affects 49.1 % of malignant brain tumors, and despite standard treatment, patients diagnosed with GBM have a dismal prognosis, a high rate of recurrence after tumor resection and poor survival. Since 2016, the World Health Organization (WHO) has included molecular biomarkers in the classification of these tumors, as knowing the heterogeneity and possible genetic changes allows for new therapeutic possibilities. The purpose of this review was to provide an overview of epidemiology and classification, as well as changes in signaling pathways resulting from genetic alterations that affect crucial factors in tumorigenesis, response to treatment and prognosis. Therefore, understanding and characterizing the vast genetic heterogeneity of GBM, both genetic and epigenetic alterations, enable a greater comprehension of the pathogenesis of this tumor, potentially helping to bring new therapeutic approaches and personalization of treatment through the different genetic alterations in each patient.